Surviving in Veranda of Mecca: The Existence of Chinese Community in Gampong Peunayong, Kuta Alam District, Banda Aceh - Yuni Saputri (Journal of Islamic History and Manuscript, 2023)
This research is entitled Surviving in the Veranda of Mecca: The Existence of Chinese Community in Gampong Peunayong, Kuta Alam District, Banda Aceh. This research aims to understand the social situation of the Tinghoa ethnicity and the relationship between the Chinese ethnicity and the People of Aceh, as well as understand the life of the Chinese ethnicity while implementing Islamic law in Aceh. This study uses a descriptive qualitative research method. The data collection techniques for this research were observation, interviews, and library research. The object of this study is the people of Gampong Peunayong, both Acehnese and Chinese ethnicity. The results show that Chinese ethnicity in Gampong Peunayong provided responses generated through interactions between Chinese and Acehnese. Responses and feedback from the public varied depending on their respective perspectives in the form of positive and negative responses.